The Cambridge Companion to Environmental Humanities / Ed. - Cohen, Jeffrey Jerome Ed.; Foote, Stephanie Ed. (Singapore : Cambridge University Press, 2021)
"What is Environmental Humanities? Over the last three decades, humanities scholars working on environmental matters have moved beyond field-specific and well-delineated descriptors like "environmental history" or "literature and the environment," subdisciplines that had often been outliers in the curricula of History and Literature departments. These scholars produced groundbreaking interdisciplinary work that challenged the primacy of standard narratives of the cultural reproduction of the vexed category of nature, and helped to usher in what we now label the environmental humanities (or EH). EH is a lively and capacious domain of inquiry that includes researchers and writers in Literature, Languages, History, Anthropology, Urban Planning, Philosophy, Political Science, Education, Religion, Classics, Creative Writing, Geography, and Landscape Architecture, as well as scholars of Race and Gender Studies. Working within and across conventional disciplines, EH has over the last decade or so spun out a dazzling set of conceptual and theoretical problems, drawing on feminist, queer, postcolonial, urban, oceanic, posthuman, nonhuman, elemental, prismatic, geologic, digital, indigenous, new materialist, energy, and object oriented ontology theories. In each of these riotous theoretical inquiries, EH scholars have challenged the disciplinary conventions that have shaped and limited how we understand and can talk to one another about key terms like "nature," "culture," "matter," and "representation.""--
Keywords: Human Ecology and the Humanities; Environmental Sciences -- Philosophy; Environmental Justice; Nature (Aesthetics)